Leal, Santos & C. - A história da fábrica através do seu biscoito : produção, venda, consumo e musealização - Nery, Olivia Silva (2020)
This Thesis deals with the history of the Leal Santos & Co factory, founded in 1889, in Rio Grande city, state of Rio Grande do Sul, and in Lisboa (Portugal). The main issue it is to undestand the history of the factory - which started its activities producing pickled and cookies - through its biscuit, and what role Leal Santos played in the regional and national industrial scene between 1889-1918. Through an interdisciplinary study, also based on the issues of Business History, this work seeks to understand the trajectory of this company through the product that was essential in its construction and consolidation in the national market, in the field of cookies. For this, I used the press, advertising and narratives as sources to trace what I called the biographical trajectory of the biscuit. From there, I traced the process of creating the factory, the industrial scenario of the period, the contribution of Leal Santos in the field of industrial cookies, and the symbolic and distinctive values attributed to this product. The methodology used during this research was, fundamentally, Content Analysis, which provided a quantitative and qualitative investigation of the data. Divided into four parts, which correspond to the life stages of this cookie, the work presents how its founders founded the factory within an industrialization scenario, both in Brazil and in Portugal; how the press helped in the process of building a business image linked to Belle Époque's progress and modernity; and how Leal Santos used advertising and the press to produce and sell a product of social distinction. And yet, even after the end of their production (1960s) Leal Santos cookies continued to be a memorial and identity reference of the period studied and how their musealization can be seen as part of the relationship between factory and society. This analysis allowed us to understand that Leal, Santos & Co Factory., despite being located in the extreme south of Rio Grande do Sul, had an important contribution in the industrial scenario of the region, and also of the country, especially in the biscuit business - contributing actively for the consolidation of that market. This research also concluded that Leal Santos was a family business resulting from its time, created and shaped within the values and needs of the period, as well as a company in Rio Grande do Sul that consolidated itself, through the biscuit, in the national scene as a company of quality, progress and modernity.